Featured Product Strategies in Indragiri Hilir Regency - Zulkarnain, Zulkarnain; Indarti, Sri; Wasnuri, Rendra; Febriansyah, Irfan Wirya (Program Pascasarjana, Universitas Riau, 2019)
Micro, Small and Medium Enterprises (UMKM) in the national and regional economy occupy a strategic position. This is because the 10 subdistricts have a very significant contribution in providing employment opportunities and employment, expanding business opportunities and equity, and are a source of income for most people. Thus, the development of UMKM is a necessity in the framework of improving the people's economy, acceleration and growth as well as improving the regional economy. UMKM cover almost all sectors/sub-sectors of the regional economy. In each sector/sub-sector of the economy includes commodities, products or types of businesses that are very diverse. In order to further enhance the effectiveness of coaching for the development of UMKM, it is necessary to focus on the commodity, product or type of business that is featured, so that the fostering and development program becomes more focused. Thus the Government can prioritize economic policies through the development of featured products in an area as an effort to create jobs and improve community welfare in order to reduce the number/level of poverty in the area. In the end, it is expected to increase local economic growth and be able to become a commodity that has export value